Roles of hepatic stellate cells in NAFLD: From the perspective of inflammation and fibrosis - Wang, Man; Li, Lei; Xu, Yannan; Du, Juan; Ling, Changquan (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) has become one of the most common diseases and severe problems worldwide because of the global increase in obesity, dyslipidemia, hypertension and type 2 diabetes mellitus. NAFLD includes a wide spectrum of liver diseases, which histological forms range from non-alcoholic fatty liver (NAFL), which is generally nonprogressive, to nonalcoholic steatohepatitis (NASH), which can progress to chronic hepatitis, liver cirrhosis, and sometimes hepatocellular carcinoma. Unlike NAFL, As the progressive form of NAFLD, NASH is characterized by the presence of inflammation with or without fibrosis in addition to hepatic steatosis. Although, it is widely known and proved that persistent hepatic injury and chronic inflammation in the liver activate quiescent hepatic stellate cells (HSCs) and lead to hepatic fibrosis, the three-step process of ‘‘inflammation-fibrosis-carcinoma’’ in NAFLD has not been investigated and clarified clearly. In this process, the initiation of inflammation in the liver and the function of various liver inflammatory cells have been discussed regularly, while the activated HSCs which constitute the principal cells responsible for fibrosis and their crosstalk with inflammation seem not to be investigated specifically and frequently. And accumulated evidences suggest that HSCs can not only activated by inflammation but also participate in the regulation of liver inflammation. Therefore, it is necessary to investigate the unique roles of HSCs in NAFLD from the perspective of inflammation and fibrosis. Here we review the pivotal effects and mechanisms of HSCs and highlights the potential value of HSCs-targeted treatment methods in NAFLD.